2004
DOI: 10.1103/physrevb.70.172106
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of giant dielectric constant in Li- and Ti-doped NiO

Abstract: We have measured optical reflectivity of Li and Ti doped NiO (LTNO) in the infrared range at various temperatures. A Drude-like absorption is found at low energy, ω < 100 cm −1 and its spectral weight increases substantially as temperature decreases. This observation and DC-resistivity result show that LTNO has a conductive grain and resistive boundary. Such composite structure provides evidence of the Maxwell-Wagner (MW) mechanism as the origin of the high dielectric constant εo. We propose a three-phase gran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The design and development of CP materials with high dielectric constant (>10 3 ) and low loss tangent (<10 −1 ), as well as high thermal stability for high-end ceramic capacitors has become a current hot research area. A range of promising CP materials have been intensively studied, such as NiO, 1,2 ferroelectrics, 3–5 CaCu 3 Ti 4 O 12 (CCTO), 6,7 ACu 3 Ti 4 O 12 (ACTO), 8,9 etc. Unfortunately, their practical application in the electronics industry is restricted owing to large tan δ , strong frequency/temperature dependence of ε r , low phase transition temperature, and potential environmental contamination/or other factors.…”
Section: Introductionmentioning
confidence: 99%
“…The design and development of CP materials with high dielectric constant (>10 3 ) and low loss tangent (<10 −1 ), as well as high thermal stability for high-end ceramic capacitors has become a current hot research area. A range of promising CP materials have been intensively studied, such as NiO, 1,2 ferroelectrics, 3–5 CaCu 3 Ti 4 O 12 (CCTO), 6,7 ACu 3 Ti 4 O 12 (ACTO), 8,9 etc. Unfortunately, their practical application in the electronics industry is restricted owing to large tan δ , strong frequency/temperature dependence of ε r , low phase transition temperature, and potential environmental contamination/or other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies indicated that the performance of capacitors is enhanced since their use is critical for temporary electric storage [1][2][3][4][5] . Ceramic capacitors are widely used as essential components in a variety of devices, such as graphics cards and random-access memory (RAM) 13 . The dielectric properties of a material determine its suitability for various applications, especially for capacitors.…”
mentioning
confidence: 99%